ANALISIS PENGARUH TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA INDUSTRI MAKANAN DAN MINUMAN INDONESIA - Talitha Syahda; Vina Octaviani; Neryn Septy Pamelynda; Farah Margaretha Leon (Pascasarjana Universitas Halu Oleo, 2021)
This research was conducted to demonstrate the effectiveness of the implementation of corporate social responsibility by including it as an independent variable in terms of CSR spending, CSR activities, and the acquisition of CSR awards. The dependent variables in the study were financial performance, and the size of the company, the company's risk, and the age of the company were control variables. The sample size of the survey includes 18 food and beverage companies listed on the Indonesia Stock Exchange between 2015 and 2020. Data analysis methods use regular regression analysis tools. The results of this survey show that CSR awards and the age of the company affect business performance. The implications of this research are improving financial performance, building reputations, gaining a competitive advantage, and as a matter of investment consideration should investors need to consider how well the company performs in generating many awards that drive the company's productivity, as well as how long the company has been operating in order to measure the company's ability and experience in disclosing all information, including CSR disclosures.